Response to ‘Lessons from the Virtual Agora Project’ - Michael K. Briand (Journal of Deliberative Democracy, 2006)
In a recent study, Peter Muhlberger and Lori Weber found strong evidence that participants in public deliberation acquired substantial new knowledge of the issues they had prepared to discuss. However, participants in their “control” group—a group that did not discuss the issue—learned just as much as those who did discuss it. The authors concluded that, by itself, discussion did not significantly increase overall decision knowledge. Nor did discussing the issue add substantially to the change in policy views they observed. Just reading and thinking about the information they were given produced the gain in knowledge and changes in attitudes that the post-event surveys revealed.To their credit, Muhlberger and Weber note that their study focuses narrowly on the acquisition of factual “decision knowledge.” They caution that their findings do not address whether discussion promoted the acquisition of knowledge other than factual knowledge.The authors also anticipate a criticism when they concede that they did not first “establish that participants ‘really’ deliberated.” They argue that their “approach to insuring deliberation…is typical for many studies, including those that purportedly show the learning effects of deliberation….” Though understandable, this acceptance of the prevailing research conception of deliberation takes for granted precisely what needs to be the focus of critical investigation. Whether deliberation occurred is a question whose answer observers too often assume is “yes.” In fact, there has been very little discussion as to what the essential characteristics of deliberation are. Hence it is difficult to say we know when deliberation has occurred. Nor has there been much discussion concerning how to determine the quality or the effectiveness of deliberation.Until discussion of such fundamental questions produces answers that are accepted widely and to general satisfaction, even exemplary empirical studies such as Muhlberger and Weber’s will be less illuminating and less useful for practice than they might be.The authors do suggest a number of useful lessons for practice.